Trans-Colostomy Placement of a Button Gastrostomy Tube for Malignant Bowel Obstruction in Patients with Peritoneal Carcinomatosis - Ozawa, Mizuki; Sone, Miyuki; Arai, Yasuaki; Sugawara, Shunsuke; Itou, Chihiro; Kimura, Shintaro; Okamoto, Daisuke; Kusumoto, Masahiko (The Arab Journal of Interventional Radiology, 2021)
Purpose The aim of the study is to evaluate the feasibility, safety, and efficacy of the trans-colostomy placement of a button gastrostomy tube for patients with malignant bowel obstruction due to peritoneal carcinomatosis.Material and Methods Data from seven consecutive patients who presented with malignant bowel obstruction due to peritoneal carcinomatosis involving the colostomy site and underwent trans-colostomy button gastrostomy tube placement between 2013 and 2020 were retrospectively reviewed. We assessed technical and clinical success rate, procedure time, duration of improvement, and complication rate.Results The technical success rate of the trans-colostomy button gastrostomy tube placement was 100%, and average procedure time was 25 minutes. Clinical symptoms of malignant bowel obstruction resolved in four out of seven (57%) patients. Average duration of improvement in the four patients with clinical success was 170.8 days. There were no complications associated with the procedure.Conclusion Trans-colostomy button gastrostomy tube placement might be a safe and feasible treatment option for patients with malignant bowel obstruction due to peritoneal carcinomatosis.
Keywords: malignant bowel obstruction; button gastrostomy tube; peritoneal carcinomatosis